EZ-Train Mobile App / Siti Aishah Sha'ari ... [et al.] - Sha'ari, Siti Aishah; Itor, Alirah; Mohd Shukor, Muhammad Faizzudin; Madehie, Nur Hazeera; Mohamad Musa, Nurafiqah (2021)
"Ez-Train Mobile App" is an application which is specially created for train users such as KTM, LRT, MRT and Monorail. Ez-Train's objectives are to introduce an E-wallet system for consumers to purchase the ticket online and scan the QR code to enter the train, facilitate consumers to find the closest station around them, and ease consumers to arrange their time accordingly the train's schedule. The most significant novelty is that no one has yet created such an application for the use of train users that can gain a variety of uses. This is because up until now, there is still no use for an application for the train users that are multi-purposes like this mobile application. This application special criteria, as what we have mentioned above it is not just can be used by users who only want to use KTM, in fact it can also be used for the LRT, MRT and Monorail services. The usefulness of the Ez-Train's is the top-up can be done by using online banking system that will be linked with this application where you can put an amount of money. Plus, when they top-up their account, they will collect loyalty points and discounts. Other than that, users can track the train through the map and they will get all the information about the train's location live, including the tracking number on which the train is arriving, the scheduled arrival times, the expected departure times, next upcoming stop, the train's intended destination and all intermediate station updates. Users also can check the availability of the train's seat and choose their seat. This product specification allows new users to register and sign in with multiple social media such as Facebook, Instagram, Twitter and Email.